Control layer security: a new security paradigm for cooperative autonomous systems - Guo, Weisi; Wei, Zhuangkun; González-Villarreal, Oscar J.; Perrusquía, Adolfo; Tsourdos, Antonios (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Autonomous systems often cooperate to ensure safe navigation. Embedded within the centralised or distributed coordination mechanisms are a set of observations, unobservable states, and control variables. Security of data transfer between autonomous systems is crucial for safety, and both cryptography and physical layer security methods have been used to secure communication surfaces - each with its drawbacks and dependencies. Here, we show for the first time a new wireless Control Layer Security (CLS) mechanism. CLS exploits mutual physical states between cooperative autonomous systems to generate cipher keys. These mutual states are chosen to be observable to legitimate users and not sufficient to eavesdroppers, thereby enhancing the resulting secure capacity. The CLS cipher keys can encrypt data without key exchange or a common key pool, and offers very low information leakage. As such the security of digital data channels is now dependent on physical state estimation rather than wireless channel estimation. This protects the estimation process from wireless jamming and channel entropy dependency. We review for first time what kind of signal processing techniques are used for hidden state estimation and key generation, and the performance of CLS in different case studies.
Keywords: Cybersecurity; wireless communication; control theory; estimation; autonomous systems